2016
DOI: 10.1111/tid.12601
|View full text |Cite
|
Sign up to set email alerts
|

Role of mTOR inhibitors for the control of viral infection in solid organ transplant recipients

Abstract: Appropriate post-transplant immunosuppressive regimens that avoid acute rejection, while reducing risk of viral reactivation, have been sought, but remain a chimera. Recent evidence suggesting potential regulatory and antiviral effects of mammalian target of rapamycin inhibitors (mTORi) is of great interest. Although the concept of an immunosuppressive drug with antiviral properties is not new, little effort has been made to put the evidence together to assess the management of immunosuppressive therapy in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 105 publications
0
44
0
3
Order By: Relevance
“…Interestingly, the recipients in group 1 and in particular group 2 showed superior results in terms of virus infection compared with group 3. Rejection and infection are regarded as a pair of contradictory players in the field of organ transplantation, and the immunosuppressive therapy is usually related to compromised anti‐infection capability . It is worth noting that no recipients in group 2 had acute rejection and virus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the recipients in group 1 and in particular group 2 showed superior results in terms of virus infection compared with group 3. Rejection and infection are regarded as a pair of contradictory players in the field of organ transplantation, and the immunosuppressive therapy is usually related to compromised anti‐infection capability . It is worth noting that no recipients in group 2 had acute rejection and virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Rejection and infection are regarded as a pair of contradictory players in the field of organ transplantation, and the immunosuppressive therapy is usually related to compromised anti-infection capability. 39,40 It is worth noting that no recipients in group 2 had acute rejection and virus infection. Whether donors at this age are more advantageous in the interaction of rejection and infection still needs to be investigated, and our study at least showed that donor livers younger than 3 months old have decreased chance of acute rejection and virus infection compared with older donors which are considered to be more mature.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral prophylaxis is administered to prevent primary infection in CMV‐seronegative KTR transplanted from CMV+ donors, as well as in patients undergoing intensive immunosuppression (eg, thymoglobulin induction) . The incidence of CMV infection has been reported to decrease in patients treated with mammalian target of rapamycin–targeting drugs . On the other hand, posttransplant surveillance of viremia in CMV+ KTR allows early detection of viral replication and administration of preemptive therapy …”
Section: Introductionmentioning
confidence: 99%
“…8 The incidence of CMV infection has been reported to decrease in patients treated with mammalian target of rapamycintargeting drugs. 9,10 On the other hand, posttransplant surveillance of viremia in CMV+ KTR allows early detection of viral replication and administration of preemptive therapy. 11,12 Ultimately, control of CMV replication in KTR depends on the fitness of the individual immune response to keep the pathogen at bay under immunosuppressive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…56 Specifically, the use of antilymphocyte antibodies (a frequent component of induction therapy) that ablate lymphocyte function for prolonged periods and prompt the elaboration of proinflammatory cytokines is associated with CMV, as they both allow for reactivation of latent virus and enhance viral replication. 58 In addition to the net state of immunosuppression as defined by the choice of immunosuppression, risk factors for the development of CMV include CMV-seropositive donor, especially if the recipient is CMV seronegative, allograft rejection, coinfections with other viruses (HHV 6), host factors (including genetic factors), and severe hypogammaglobulinemia. Although calcineurin inhibitors (CNIs) are not drivers of reactivation, they do allow for amplification of reactivated virus; tacrolimus is more potent than cyclosporine.…”
Section: Pathogenesis/risk Factorsmentioning
confidence: 99%